Learning styles among university students and learning-centered teaching - Gargallo-López, Bernardo; Pérez-Pérez, Cruz; Verde-Peleato, Irene; García-Félix, Eloïna (Revista electrónica de investigación y evaluación educativa, 2017)
The aim of this work was to assess the impact of learning-centered methods, implemented by four professors into the learning styles of some students on the Educational Processes and Contexts, a course of the Master’s Degree in Secondary Education Teaching at the University of Valencia (Spain). Another aim was to analyze the students’ assessment employed methods. The sample included 117 subjects from this Master’s Degree in 2014-15, divided into four groups from four different specialties. A quasiexperimental design was used along with pre-test/post-test measures with the ILS (Inventory of Learning Styles) questionnaire (Vermunt, 1994). Students also assessed the methods used by their professors with a quantitative questionnaire. The professors followed learning-centered methods with different methodological formats with the four groups. Significant improvements were found in many of the variables measured by the questionnaire (deep learning, self-regulation, personal interested-based learning direction, using knowledge, cooperation, etc.) in the four student groups, and the pre-test/post-test differences were bigger in groups 1 and 4 than in groups 2 and 3. The inter-group comparisons reflected significant differences in the pre-test among all four groups, which did not appear in the post-test so all the groups were equal after applying the learning-centered methods. The students positively assessed the used methods. The results confirmed the positive influence of learning-centered methods on students’ learning styles and provided some ideas to improve teaching-learning processes with university students.